Analisis Efektivitas Kerja Karyawan Divisi Yan HC PT. PLN (Persero) - Allen Maulani; Nuruni Ika Kusuma W (JURNAL RISET MANAJEMEN (JURMA), 2023)
Purpose – This study aims to determine whether the performance of Yan HC division employees at PT. PLN (Persero) has been effective. Methodology – The method used is observation, documentation and interviews with all employees of Yan HC PT. PLN (Persero), totaling 9 people. The data that has been obtained from the research results is processed using a qualitative description to determine the effectiveness of the performance of employees of PT. PLN (Persero). Findings – The results show that the effectiveness of employee performance is good. Some things still need to be improved for the sake of convenience in the future. A more computerized work system is needed at PT. PLN (Persero). Originality/Novelty – The research was conducted by direct observation during the internship period which was conducted from March to July at the Yan HC division of PT. PLN (Persero). Implications – The implication for employees and companies is increasing performance effectiveness. With this increase in effectiveness, it is hoped that it will minimize the effort, time and funds that must be spent by employees and the company. For companies, it is necessary to provide the facilities needed by employees in order to increase work effectiveness.